Chemical Composition and Antioxidant Activity of Stingless Bee Propolis from Different Extraction Methods - Basyirah Md Zin, Nur; Azemin, Azierah; Muslim Mohd Rodi, Muhammad; Suryati Mohd, Khamsah (International Journal of Engineering and Technology, 2018)
Propolis has been used as therapeutic agent since ancient time and considered as high value materials. In order to obtain maximum yield of extract production with excellent biological activity, extraction techniques need to be established. This study aimed to optimize extraction protocol and screen total phenolic, total flavonoid and antioxidant activity. Propolis was collected from Apiary of UniSZA, Besut Campus. Propolis was extracted with 70% and 95% ethanol using different extraction methods, which were: maceration, sonication and soxhlet. Total phenolic content and flavonoid content were determined using spectrophotometric method. The antioxidant activity was evaluated using 2, 2- diphenyl-1-picrylhydrazyl (DPPH assay). Extraction by maceration at 5 days of ethanolic extract showed the highest total phenolic content of 46.68Â±2.08 mg gallic acid equivalents per g extract propolis (GAE/g). While, 70% ethanolic from 30 minutes of sonication method displayed the highest total flavonoid content compare to that 95% ethanol with value 107.27Â±4.10 mg quercetin equivalents per g extract (QE/g). The lowest total flavonoid content was 95% ethanolic extract by soxhlet extraction at 6 hours (26.71Â±3.58QE/g). The propolis extract of 70% ethanol from sonication (30 minutes) also showed a good antioxidant activity with IC50 value 11Â±0.55Î¼g/mL Trolox equivalents per g extract. Finding from this study showed the most specification of extraction methods is important to extract specific compounds and quality extract for propolis.Â